Transformational and Transactional Leadership in the Polish Organizational Context: Validation of the Full and Short Forms of the Multifactor Leadership Questionnaire - Bajcar, Beata; Babiak, Jolanta (Frontiers in Psychology, 2022)
The Multifactor Leadership Questionnaire (MLQ 5X Short) is the most frequently used leadership measure in scholarship and organizational practice. However, so far it has not been validated in the Polish context. Therefore, the present study aimed to validate and shorten the MLQ (5X Short) in the Polish organizational setting. A total sample of 1065 employees (572 women and 493 men) from different organizations took part in two sessions of an online study. Respondents were between 18 and 70 years old (M = 40.1; SD = 12.9) with an average job tenure of 17.00 years (SD = 12.1). In subsample 1 (n = 539), using exploratory factor analysis, a three-factor structure of the MLQ full form (MLQ-FF) was established, comprising transformational-supportive, inspirational goal-oriented, and passive-avoidant leadership. Based on qualitative (i.e., content analysis) and quantitative criteria (psychometric parameters), we constructed an 18-item MLQ short form (MLQ-SF). Both forms were supported by the confirmatory factor analysis in subsample 2 (n = 526). The MLQ-FF and MLQ-SF factors displayed acceptable to high levels of item-related parameters (e.g., intra-class, inter-item, and item-total correlations), as well as scale-related reliability (e.g., internal consistency, temporal stability). Both forms indicated high convergent and predictive validity examined by correlations with authentic leadership and employee’s work outcomes (i.e., work satisfaction, work effectiveness, work engagement, and organizational commitment) (subsample 3; n = 691). Our study provided the full and the short form of the MLQ as reliable and valid instruments, potentially suitable to measure leadership styles in academic research and organizational practice.